MODELING ALGORITHMS DEVELOPMENT OF DEVICE FUNCTION OF THE FUEL CHARGE AND INTERACTION WITH A FUEL MAIN - Koshevoy, N. D.; Mikhailov, A. G. (Radio Electronics, Computer Science, Control, 2012)
In this article the construction principles of device function modeling algorithms of the fuel charge are considered. The functioning dynamic models of parameters measurement systems of fuel are submitted.